Comparative analysis of antibiotic resistance patterns and virulence genes in Staphylococcus aureus strains isolated from clinical samples at Hue University of Medicine and Pharmacy Hospital - Ung, Thi Thuy; Nguyen, Thi Khanh Linh; Dinh, Thi Hai; Hoang, Thi Minh Ngoc; Nguyen, Hoang Bach (Tạp chí Y Dược Huế, 2025)
Background: Composite materials are widely used in aesthetic dental restorations due to their advantages, including minimal invasive preparation, high mechanical strength, adhesive durability, biocompatibility, time and cost-effectiveness. In composite layering techniques, material thickness significantly impacts the aesthetic outcome. Objectives: This study investigates the effect of enamel-shade composite thickness on the final color values of restorations using a two-layer technique to replace enamel and dentine. Materials and Method: Forty-five A2 enamel-shade composite discs were created from three composite groups: DenFil (Vericom Corp.), Harmonize (Kerr), and Beautifil II (Shofu Inc.) with five thicknesses: 0.3, 0.5, 1.0, 1.5, and 2.0 mm. Parameters measured included translucency, chroma, value, and color difference. Samples were photographed against black-white backgrounds and a 3.0 mm thick OA3 dentine-shade composite background. Color parameters (L, a, b) were collected using image analysis software to assess translucency, chroma, value, and color difference. Results: Translucency and chroma were inversely proportional to thickness for the three composite groups. With value, in the DenFil group, increased thickness decreased value, while no statistically significant correlation was found in the other two groups. When comparing the restoration color with the same enamel-shade composite thickness, no significant differences were found between Harmonize and Beautifil II, but DenFil significantly differed. Conclusion: In the two-layer technique for replacing enamel and dentine, enamel-shade composite thickness affects restoration color characteristics, varying among composite materials.